The implementation of the Student Response System (SRS) Kahoot! in EFL classes and its effects on reading comprehension - Joe Adrián Narváez Paguay; Juan José Santillán (Innova Research Journal)
Improvement of teacher-student class interaction has been obtaining greater progresses thanks to technological development with the addition of practical resources and modern facilities in educational institutions. The use of game-based response systems for enhancing language skills inside an EFL classroom has reported benefits mainly for certain particular skills like grammar and sentence structuring.  In this study, the online gaming platform Kahoot! was used specifically for enhancing the reading comprehension skill through a period of nearly three months on students of A2 level from Universidad de Cuenca in Ecuador. The intervention of the Kahoot! website focused on the comprehension and remembering of specific details by means of quizzes. The research design of this study used a mixed-method based on the Hypothetico-Deductive approach to research and data collection instruments, as well as their further analysis and interpretation. Pre and posttests were used in order to compare the results before and after the methodology. The outcomes revealed a statistical improvement with favorable effects regarding the pre and posttests and also a general learner acceptance towards the stated methodology. Further research is suggested on the use of Kahoot! for reading comprehension improvement purposes and its continuous use as a supporting tool for remembering specific details of texts, together with other subskills which could possibly be benefitted from this methodology in the field of EFL instruction.